Efektivitas Pemasangan Tanda Batas Atau Patok Pada Batas Tanah Untuk Menjamin Kepastian Hukum - Mourisya Faida Anjarsari; Romlan; Tri Susilowati (GLOBAL SCIENTS PUBLISHER, 2025)
In the current era, people need to be careful about land boundary disputes. In determining land boundaries, witnesses are required, including land owners, neighboring neighbors and village officials. Installing land boundary signs can prevent land boundary disputes and ensure legal certainty. Problem. How to install boundary signs correctly according to statutory regulations. Benefits of installing land boundary signs. The approach method uses normative juridical, research specifications are analytically discrete. Data sources are primary data and secondary data. Data collection methods are observation and literature study. Research results . The correct way to install boundary signs is in accordance with the Basic Law for determining land parcel boundaries, namely article 19 of the Basic Agrarian Law and article 3 paragraph (2) of Government Regulation Number 10 of 1961 Jo Chapter IV second part paragraph 3/article 17, Article 18, Article 19 of Government Regulation of the Republic of Indonesia Number 24 of 1997 concerning Land Registration. The benefits of installing land boundary signs are to ensure legal certainty, avoid land disputes, and make it easier for BPN officers to take measurements when land registration is carried out.